A compact dual-band bandpass SIW filter using uniplanar combination of the CRLH and resonant type metamaterials. Issue 4 (2nd October 2018) - Sharma, Jigyasa; Kumar, Dhirendra; De, Asok
ABSTRACT: A new manner of obtaining dual bandpass behaviour in substrate-integrated waveguide (SIW) using a uniplanar combination of composite right/left-handed (CRLH) transmission line and complimentary double split single ring resonator (CDSSRR) is presented and analysed in this paper. The proposed dual band structure has the advantage of miniaturisation due to the presence of both the passbands below the characteristic cutoff frequency of the SIW.A high passband transmission zero overcomes the poor frequency selectivity, and the two resonant frequencies are independently controllable. There are very low insertion losses in both passbands as compared to DGS structures and fabrication simplicity is ensured due to an intact ground. The potential for application of the proposed structure to the design of completely planar miniaturised dual band bandpass metamaterial filters has been verified by fabricating a two-stage filter based on the proposed combination. The measured results are in good agreement with the simulation results.